Influence of Fabric Structure and Properties on Thermal Comfort of Medical Protective Clothing (Journal of Fiber Bioengineering and Informatics, 2023)
Medical protective clothing is an important personal protective equipment for medical staffs, especially in the pandemic. This research paper studied the effect of structure properties (material, yarn linear density and fabric thread density) of cotton and polyester fabrics on human thermal comfort. The main methodology entails using a CAD software to simulate the thermal comfort value of the individual when they wear a medical protective clothing made of 10 plain-woven fabric types. The normal effective temperature formula is used to simulate the clothing microclimate for evaluating the thermal comfort value. Three environment settings, indoor hospital conditions, outdoor environment of Manchester, UK in July and the outdoor environment of Hong Kong in July, are used in the simulation. Then analysis was conducted on the simulation results. The results indicate that yarn linear density has the biggest effect on the thermal comfort value. The cotton fabric with a yarn linear density of 131 Denier and thread density of 209/inch has the best thermal comfort performance. It also meets the physical strength requirements of surgical gown son EN 13795-1:2019. The result demonstrates that the moisture management capability of the fabric that affects dampness sensation of human body, is the most important ability to improve the thermal comfort value, and the influence of the yarn structure needs to be taken into consideration in the future studies.
Keywords: Personal protective equipment; Textile CAD technology; Mathematical modelling; Mathematical analysis